The Influence of Counseling About Menopause on the Success of Self-Mental Treatment at the Dolo Community Health Center, Dolo District, Sigi Regency, Central Sulawesi Province - Siyamti (Journal for Research in Public Health, 2024)
There are so many cases of women experiencing psychological problems when facing menopause. When the woman cannot overcome her psychological condition, it will automatically affect her physical health condition. This requires health education in order to achieve self-mental treatment success. The purpose of this study was to determine the relationship of the influence of counseling about menopause on the success of self-mental treatment. This study used the pre-experiment method with pre-test and post-test experiments. The population studied were all women who were experiencing menopause at the Dolo Health Center, Dolo District, Sigi Regency, Central Sulawesi Province, using a purposive sampling technique, a sample of 70 respondents was obtained. The results of data analysis using the Wilcoxon Signed Rank Test statistically obtained that Exact Sig. (2-tailed) p value < 0.05 then H_0 was rejected, and H_1 was accepted, meaning that there was an effect of counseling about menopause on the success of self-mental treatment at the Dolo Health Center, Dolo District. Sigi Regency, Central Sulawesi Province. The counseling process occurs through knowledge transfer. Knowledge about menopause in women is very important because it will be the basis for carrying out an action including self-mental treatment. Increasing the implementation of self-mental treatment can encourage women to be more prepared in dealing with the symptoms of menopause that arise and can maintain their mental health.